El método Willems y las emociones de los niños de inicial II paralelo B de la Unidad Educativa “Dr. Gabriel García Moreno” del cantón Guano - Zuñiga Santos, Odalis Aracely (2024)
The present investigative work refers to The Willems method and the emotions of the children of initial II class B of the Educational Unit “Dr. Gabriel García Moreno” from the Guano city, which main objective is to analyze the two study variables through the qualitative paradigm and highlights the importance that the use of musical activities based on this method allows the comprehensive and healthy training of students. The methodology used was qualitative, non-experimental, basic, field, correlational and transversal design; with a sample of 14 girls and 8 boys, to whom an observation sheet was applied and to provide more evidence, the 4 primary school teachers were interviewed. During the processing of the information obtained in the interview, a matrix of relationships between categories was created and for the observation sheet the data was directly analyzed and interpreted as a story. Furthermore, another section details the correlation of the study variables in a table of qualitative relationships, with which the following results were obtained: the Willems method and emotions have a direct and significant relationship.